Difficult knowledge boundaries during requirements determination. (18th August 2020) - O'Raghallaigh, Paidi; Lane, Stephen; Adam, Frederic; Sammon, David
ABSTRACT: Academics and practitioners assume that knowledge sharing and knowledge integration are critical to effective team performance. However, the findings from empirical studies are at best mixed and in some cases contradictory. This study investigates the complex relationships between these factors as well as the moderating role of project objects (e.g., design outputs such as personas, journey maps, use cases, prototypes, etc.) in small project teams. Our case study explores how knowledge-based interactions and object usage coexist in impacting the performance of a small cross-disciplinary project team tasked with deciding the requirements for a connected health information system. A conceptual model is presented that illuminates some empirical nuances that are not addressed within extant literature. The paper uses the concept of boundary objects to explain these nuances. While static boundary objects supported lower levels of communication, malleable boundary objects were required for more in-depth communication.